Fractional order models of infectious diseases: a review - Khalil, M.; Said, M.; Osman, H.; Ahmed, B.; Ahmed, D; Younis, N; Maher, B; Osama, M; Ashmawy, M (SPC Journal of Environmental Sciences, 2019)
The aim of this paper is to present a succinct review on fractional order models of infectious diseases. Fractional order derivative is a potential tool which gives a better understanding of the impact of memory on spread of infectious diseases. This paper reviews different infectious diseases models with constant, variable or complex fractional order. Fractional order models with time delay are presented in this paper as well. We argue that, such models are essential for decision makers in health organizations.Â Â Â